The Role of Southern Actors in Global Governance: The Fight against HIV/AIDS - Sonja Bartsch; Lars Kohlmorgen (German Institute of Global and Area Studies (GIGA), 2007)
This paper analyses the role of actors from developing countries in global processes of policy making and governance. To systematically examine the channels of influence of Southern actors and the interactions in global governance it develops the concept of interfaces. It differentiates between organisational, discoursive, legal and resource-transfer interfaces in global governance. This approach is exemplified in the analysis of a specific field of global governance, the global fight against HIV/AIDS. The paper examines the role of Southern governments and non-state actors in the central organisations of global health, their influence in debates and discourses on strategies to fight HIV/AIDS, and the financing mechanisms that were introduced to fight HIV/AIDS in the developing world. It shows that albeit actors from Northern countries dominate global governance in general, in particular areas the current institutional setting of global governance provides significant opportunities for rather weak actors such as civil society organisations and governments from the South to influence strategies and policies. – – Dieser Beitrag analysiert die Rolle von Akteuren aus den Entwicklungsländern (dem Süden) in der globalen Politik und Governance. Zum Zwecke der systematischen Analyse der Einflusswege der südlichen Akteure und der Interaktionen bei Global Governance wird ein Schnittstellenkonzept entwickelt, das zwischen organisationalen, diskursiven, rechtlichen und Ressourcentransfer-Schnittstellen differenziert. Als Beispiel erfolgt die Untersuchung eines spezifischen Bereiches Global Governance: des globalen Kampfes gegen HIV/AIDS. Der Beitrag analysiert die Rolle südlicher Regierungen und nichtstaatlicher Akteure in den zentralen Organisation der globalen Gesundheitspolitik, deren Einflüsse auf die Debatten und Diskurse über die Strategien zur Bekämpfung von HIV/AIDS in den Entwicklungsländern entwickelt wurden. Es wird gezeigt, dass - trotz einer generellen Dominanz von Akteuren aus den Industrieländern bei Global Governance - in bestimmten Bereichen grundsätzlich schwache Akteure wie zivilgesellschaftliche Organisationen und südlichen Regierungen aufgrund des spezifischen aktuellen institutionellen Setting die Chance haben, Einfluss auf die Politiken und Handlungsstrategien auszuüben.
Keywords: 300; North-South relations; global governance; HIV/AIDS; global health; civil society; power relations; interfaces; Global Governance; AIDS; Nord-Süd-Beziehungen; Gesundheitspolitik; Welt